KRISIS MONETER 2008: PERAN PEMERINTAH DAN KEBIJAKAN ISLAM - Disyah Adelia; Ghina Rizki Zaidah; Maya Eka Rahma Sari (LP2M STAI Imam Asy Syafii Pekanbaru, 2023)
The monetary crisis in the United States in 2008 was caused by credit problems in the property sector which resulted in several financial institutions going bankrupt. This problem has an impact on the global economy. The aim of this research is to analyze monetary events in 2008 and the solutions provided by the government, as well as solutions that can be applied from an Islamic perspective. This research uses library research, so the method used is library research. Literature study searches using journals, books, documents, magazines and other sources without any field research. The research results show that the government's role is very necessary in overcoming the monetary crisis. With this, the government and central bank are making efforts to overcome the crisis by reallocating the budget, reducing the prices of basic commodities which have become expensive. Meanwhile, the solution if a monetary crisis occurs is not to apply an interest system in financing and to apply zakat to overcome economic problems.